Екологічні проблеми сільського господарства Карпат - Топольний, Ф.; Гелевера, О.; Моспан, С.; Моспан, Г.; Чепур, С. (Праці наукового товариства ім. Шевченка, 2003)
Розглянуто особливості технологій вирощування найпоширеніших сільгоспкультур в Українських Карпатах. Висвітлено причини низької
ефективности рільництва та заходи щодо підвищення урожайности
картоплі й лучних угідь. Запропоновано перспективні напрямки
розвитку аграрного виробництва й покращання екологічної ситуації в
Українських Карпатах. The technological features of cultivation of the most widespread cultures in the Ukrainian
Carpathians are analysed. The reasons of low efficiency of agriculture are indicated and
receptions for increase of productivity of a potatoes and efficiency of meadow cultures are
planned. Perspective directions of development for agrarian manufacture and improvements of
an ecological situation in the Ukrainian Carpathians are offered.